KOMUNIKASI POLITIK CALON LEGISLATIF DALAM PEMILIHAN UMUM ANGGOTA DPRD KABUPATEN KENDAL. (Studi Perbandingan Strategi Kampanye Calon Legislatif PKB Berlatar Belakang Keluarga Ulama Dan Keluarga Biasa Pada Pemilu Legislatif DPRD Kabupaten Kendal Tahun 2014 - Rizkyyawan, Nicky Dwi; Harsasto, Priyatno; Retno, Nunik (Journal of Politic and Government Studies, 2014)
This research is motivated because of the emergence of the phenomenon which in the year 2014 was a year of political and legislaif many candidates vying to attract the sympathy of the public. The number of candidates from the National Awakening Party, will be difficult to obtain an absolute victory for either candidate, so as to get a lot of support is needed a way to win. The problem formulation presented in this study is